2021
DOI: 10.7717/peerj.10831
|View full text |Cite
|
Sign up to set email alerts
|

Predicting maximal oxygen uptake from a 3-minute progressive knee-ups and step test

Abstract: Background Cardiorespiratory fitness assessment is crucial for diagnosing health risks and assessing interventions. Direct measurement of maximum oxygen uptake (V̇O2 max) yields more objective and accurate results, but it is practical only in a laboratory setting. We therefore investigated whether a 3-min progressive knee-up and step (3MPKS) test can be used to estimate peak oxygen uptake in these settings. Method The data of 166 healthy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 26 publications
5
29
1
Order By: Relevance
“…Chung et al (2021) found that the difference between HR at the third minute during the exercise and recovery HR at the first minute post exercise in the 3 min step test had positive correlations with . VO 2max [2]. The results of the present research are consistent with those of previous studies, demonstrating that ∆HR3 − HR4 and .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Chung et al (2021) found that the difference between HR at the third minute during the exercise and recovery HR at the first minute post exercise in the 3 min step test had positive correlations with . VO 2max [2]. The results of the present research are consistent with those of previous studies, demonstrating that ∆HR3 − HR4 and .…”
Section: Discussionsupporting
confidence: 93%
“…Since there is a linear relationship between HR variations before, during, and after exercise and . VO 2max [2,3,6,17,[35][36][37][38], the exercise HR test can improve the prediction of the . VO 2max model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations